Prevention of unplanned extubation in neonatal patients: Protocol for a systematic review and meta-analysis - Ludmylla Cristina de Faria Pontes; Isac Davidson Santiago Fernandes Pimenta; Gidyenne Christine Bandeira Silva de Medeiros; Daniel Guillén-Martínez; Paloma Echevarria-Pérez; Grasiela Piuvezam; Helaine Carneiro Capucho (PLoS ONE, 2025)
Unplanned extubation (UPE), defined as accidental removal of the endotracheal tube during mechanical ventilation or its replacement due to suspected obstruction or inadequate diameter, is considered the fourth most common adverse event in neonatal intensive care units (NICU). This study aimed to describe a systematic review and meta-analysis protocol that will identify and assess the effect of primary intervention measures designed to prevent UPE in NICU. A search will be carried out in the following databases: PubMed/Medline, EMBASE, Scopus, CINAHL, Cochrane Library, SciELO, and LILACS. Reviewers, in pairs and independently, will select the studies, perform data extraction and assess the methodological quality of the included studies using preestablished tools according to the type of study. The systematic review will provide evidence to present the main intervention measures used in the prevention of UPE during the care of critical neonatal patients. The systematic review and meta-analysis resulting from this protocol may provide important information regarding UPE in the neonatal population, which will help with decision-making and the implementation of safer clinical practices that focus on the reduction of adverse events, contributing to the improvement of service management and the safety of neonatal patients.